The pseudo-anonymity of the Ecloga in obitu in manuscript 1631 (BNM) (Circe de clásicos y modernos, 2018)
According to Ignacio OSORIO ROMERO (1989), the manuscript 1631 of the National Library of Mexico is the richest source of Neo-Latin literature in New Spain, during the sixteenth and seventeenth centuries. The codex is a compilation of Latin texts produced between 1585 and 1629 on the occasion of religious festivals, literary contexts or social events. There are twelve Latin poems included between folios 109 r and 120 r, of which eleven are eclogues. The first head of selection, entitled Ecloga in obitu, is anonymous. Mexican critic considers that this poem is perhaps a rhetorical exercise. However, the 28 anonymous verses contained in the codex belong to the Italian Baldassare Castiglione. The authorship of these hexameters collapses OSORIO ROMERO’s theory, published already for several years, and opens from here a series of questions that will be addressed in future research.
Keywords: eclogue; Neo-Latin Literature; Jesuits